Porous articles with rigid structure based on natural amorphous silica; Glass and Ceramics; Vol. 75, iss. 1-2 - Kutugin V. A. Viktor Aleksandrovich; Lotov V. A. Vasiliy Agafonovich; Gubanov A. V. Aleksandr Valerjevich; Kursilev K. V. (2018, 2018)
Title screen